Protein enrichment of tropical fruit residues by semi-solid cultivation (Research, Society and Development, 2022)
An effective way to properly manage agro-industrial residues from fruit processing is through their biotransformation into high value-added products. Fermentation, for example, is a technology that has proven to be efficient in converting substrates with a high content of lignin and a low amount of proteins, such as residues of vegetable origin, into protein-enriched materials. Thus, the aim was to evaluate the process of protein enrichment of pineapple residue, through semi-solid fermentation, using Saccharomyces cerevisiae yeast. The residue was crushed, fermented with 9% inoculum, and submitted to subjected to particle size and physicochemical analysis (water content, crude protein, and total soluble solids). The particle size result showed that the particle size followed a normal distribution, with an average diameter of 1.31 mm. It was verified that there was a decline in the water and total soluble solids contents of the residue, while its protein content was favored, increasing about the fermentation time. The experimental data obtained in this study showed that the action of yeasts acted beneficially on the residue, improving its nutritional value and, therefore, enabling its use in the food industry as raw material for mixtures for protein supply.